How low can we go? Influence of sample rate on equine pelvic displacement calculated from inertial sensor data. (23rd November 2020) - Pfau, Thilo; Reilly, Patrick
Abstract: Background: Low‐cost sensor devices are often limited in terms of sample rate. Based on signal periodicity, the Nyquist theorem allows determining the minimum theoretical sample rate required to adequately capture cyclical events, such as pelvic movement in trotting horses. Objectives: To quantify the magnitude of errors arising with reduced sample rates when capturing biological signals using the example of pelvic time‐displacement series and derived minima and maxima used to quantify movement asymmetry in lame horses. Study design: Data comparison. Methods: Root mean square (RMS) errors between the 'reference' time‐displacement series, captured with a validated inertial sensor at 100 Hz sample rate, and down‐sampled time‐series (8 Hz to 50 Hz) are calculated. Accuracy and precision are determined for maxima and minima derived from the time‐displacement series. Results: Average RMS errors are <2 mm at 50 Hz sample rate, <4 mm at 40 Hz, <7 mm between 25 and 35 Hz, and increase to up to 20 mm at 20 Hz and below. Accuracy for maxima and minima is generally below 1mm. Precision is 1 mm at 50 Hz sample rate, 3 mm at 40Hz and ≥9 mm at 20 Hz and below. Main limitations: Only sample rate, no other sensor parameters were investigated. Conclusions: Sample rate related errors for inertial sensor derived time‐displacement series of pelvic movement are <2mm at 50 Hz, a rate that many low‐cost loggers, smartphones or wireless sensors can sustain hence rendering these devices valid options for quantifying parameters relevant for lameness examinations in horses.